Patient Satisfaction from Dental Services Provided by Multan Medical & Dental College - Ejaz Hussain Sahu; Muhammad Umer Abdullah; Rai Tariq Masood (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: The aim of this study was to assess the level and factors influencing the level of patient satisfaction from dental services provided by Multan Dental Hospital. Methods: Study was carried out at Multan Dental hospital from 1st June to 30th July 2015. Total  256 patients over 18 years of age, participated  in  this  cross-sectional  study.  Convenient  sampling  tech- nique was used to  select  the  patients.  The  Hogan  Patient  Satisfaction  Questionnaire  was   customised, personalised and used for this dental patient satisfaction study,  and  response  through  a Likert scale including answer categories very satisfied, satisfied, neutral, not satisfied, not at all satisfied and do not know, was completed by the participants. SPSS software version 17  was  used  for  analysis. The relationship between level of patient satisfaction and the demographic variables was determined, Chi-square test was performed to  establish  the  level  of  patient  satisfaction  and  if  af-  fected by the demographic variables. Results: Total 29.3% patients said that they were very satisfied with the services. About 43.4% partici-  pants were satisfied with the services. Not satisfied with service  were  8.6%.  A  very  low  proportion  (5.9%) of patients were completely dissatisfied with the services. There were 42% males and 30% fe-  males who were satisfied with the services. About 49% of patients having an education between 6-14    years were satisfied from  the  hospital  services  while  only  9%  of  patients  having  higher  education  level were satisfied. The major proportion of  the  patients  showed  satisfaction  from  the  services  of-  fered at the hospital. Conclusion: Majority of the patients were satisfied  with  the  services  regarding  hospital  care,  dental staff provided by Multan Medical and Dental College.